Trends in mesenchymal stem cell-derived extracellular vesicles clinical trials 2014–2024: is efficacy optimal in a narrow dose range? - Wang, Yusong; Zhu, Junchi; Ma, Qimin; Zhou, Wei; Yang, Linshan; Sheng, Shuyue; Zhu, Feng; Xia, Zhaofan (Frontiers in Medicine, 2025)
BackgroundMesenchymal stem cell-derived extracellular vesicles (MSC-EVs) are emerging as promising cell-free therapeutic agents due to their immunomodulatory and regenerative properties. However, the lack of standardized protocols and dose optimization strategies has limited their clinical translation. While procedures for the isolation, expansion, and therapeutic use of mesenchymal stem cells (MSCs) have been standardized, there remains a lack of standardized protocols for the isolation and purification of EVs and exosomes (Exos).MethodsThis review Comprehensive statistical summary global clinical trials involving MSC-EVs and Exos registered between 2014 and 2024, with a particular focus on dose-effect relationships and administration routes. Data were collected from ClinicalTrials.gov, the Chinese Clinical Trial Registry, and the Cochrane Register of Studies. A total of 66 eligible trials were included after screening.ResultsIntravenous infusion and aerosolized inhalation were identified as the predominant administration methods, especially in trials targeting respiratory diseases. Notably, dose-effect results revealed that nebulization therapy achieved therapeutic effects at doses around 108 particles, significantly lower than those required for intravenous routes. This suggests a relatively narrow and route-dependent effective dose window. However, large variations in EVs characterization, dose units, and outcome measures were observed across trials, underscoring the lack of harmonized reporting standards.ConclusionThis review highlights dose-response as a critical but underappreciated gap in current MSC-EVs clinical research. The findings emphasize the urgent need for standardized dosing frameworks, potency assays, and harmonized clinical protocols to advance the safe and effective translation of MSC-EVs therapies. The analysis underscores the need for standardized protocols, global collaboration, and a deeper understanding of the biological mechanisms underlying MSC-EVs and Exos therapies to advance clinical applications and ensure safety and efficacy.